Vaccaria segetalis: A Review of Ethnomedicinal, Phytochemical, Pharmacological, and Toxicological Findings - Tian, Meng; Huang, Yuwen; Wang, Xin; Cao, Maosheng; Zhao, Zijiao; Chen, Tong; Yuan, Chenfeng; Wang, Nan; Zhang, Boqi; Li, Chunjin; Zhou, Xu (Frontiers in Chemistry, 2021)
Vaccaria segetalis is a dry mature seed of Vaccaria hispanica (Mill.) Rauschert, which belongs to the genus V. segetalis (Neck.) Garcke. There are multiple medicinal parts of V. segetalis, according to the records, including roots, stems, leaves, flowers, and seeds, which should be used together. Currently, V. segetalis is most frequently used in the treatment of menstruation, dysmenorrhea, breast milk stoppages, and chylorrhea. Numerous studies present historical evidence of the use of V. segetalis to treat several diseases and describe its beneficial effects including prolactin- (PRL-) like, estrogen-like, antitumor, antiangiogenesis, and antioxidant activity. We summarized the period from January 1980 to December 2019 regarding V. segetalis. This review paper indicates that V. segetalis has promising clinical applications. The main active ingredients of the plant have been elucidated in recent years. We summarized the previously and newly discovered pharmacological effects of V. segetalis in addition to its active ingredients, ethnopharmacological uses, and toxicological properties, and provided a focus for future research.